The Determination of Lightning Disaster Hazard Index Using Analytical Hierarchy Process - Fathul Mahdariza (Elkawnie: Journal of Islamic Science and Technology, 2017)
In order to minimize the losses caused by lightning, a lightning disaster management system is compulsory. It should provide lightning disaster information in an area to get the risk values of lightning strikes. One way is to establish a lightning disaster risk map. The disaster risk map consists of hazard map, vulnerability map and capacity map. However, lightning yet has not been included in the regulation guiding the establishment of risk map for several disasters in Indonesia. This study is conducted to develop a process to determine general hazard index for lightning disaster.